Michelangelo : biography of a genius - Bruno, Nardini (Firenze : Giunti, 1999)
From the Florence of Lorenzo the Magnificent and Savonarola to the splendor of papal Rome; the tormented life of a Renaissance genius: Michelangelo. A biography of Michelangelo Buonarroti with a chronological table of historical and artistic events and a topographical index of his works, of course entirely in English. Original title: '' Meeting with Michelangelo ''. (Dalla Firenze di Lorenzo il Magnifico e del Savonarola allo splendore della Roma papale; la vita tormentata di un genio del Rinascimento: Michelangelo. Una biografia di Michelangelo Buonarroti con una tavola cronologica degli eventi storici ed artistici e un indice topografico dei suoi lavori, natruralmente interamente in inglese. Titolo originale: ''Incontro con Michelangiolo''.)
Includes index.
Keywords: MICHELANGELO BUONARROTI, 1475-1564